Scent of Apples : A Collection of Stories - Santos, Bienvenido N. (Book collections on Project MUSE., 2015)
This collection of sixteen stories bring the work of a distinguished Filipino writer to an American audience. Scent of Apples contains work from the 1940s to the 1970s. Although many of Santos's writings have been published in the Philippines, Scent of Apples is his only book published in the United States.--Back cover.